2016
DOI: 10.3168/jds.2016-11403
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia coli and other Enterobacteriaceae in producer-distributor bulk milk

Abstract: INTERPRETIVE SUMMARYCharacterization of E. coli and other Enterobacteriaceae in producer-distributor bulk milk, Ntuli, The direct sale of milk from producer-distributor (PD) to consumers is a common practice in many countries. We characterized E. coli and other Enterobacteriaceae in PD bulk milk sold at retail points in South Africa (SA). The study highlighted that there is a potential risk of transferring drug resistant pathogenic E. coli to consumers through the food chain.Information obtained from the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 62 publications
2
33
0
1
Order By: Relevance
“…This species was also the most frequently identified among lipolytic psychrotrophic microorganisms. Considering the totality of the psychrotrophic microbiota of raw milk, Ntuli et al (2016) identified E. kobei in 0.8% of the 479 isolates. This bacterium belongs to the family Enterobacteriaceae, making it possible that the raw milk in the present study was contaminated directly or indirectly by feces.…”
Section: Ggytaccttgttacgacttmentioning
confidence: 99%
“…This species was also the most frequently identified among lipolytic psychrotrophic microorganisms. Considering the totality of the psychrotrophic microbiota of raw milk, Ntuli et al (2016) identified E. kobei in 0.8% of the 479 isolates. This bacterium belongs to the family Enterobacteriaceae, making it possible that the raw milk in the present study was contaminated directly or indirectly by feces.…”
Section: Ggytaccttgttacgacttmentioning
confidence: 99%
“…This bacterial collection included 48 isolates from irrigation water (Aijuka et al, 2015;Aijuka, 2014), 29 from irrigated lettuce (Aijuka, 2014), 118 from milk (pasteurized and unpasteurized PDBM) sold by small holder sellers (producerdistributer) (Ntuli et al, 2016) and 10 from street-vendor coleslaw purchased in Pretoria City, South Africa. All isolates collected over these studies were stored at -80°C at the Department of Food Science, University of Pretoria, South Africa in Tryptone Soy Broth (TSB)(Biolab Diagnostics (Pty) Ltd, Midrand, South Africa) containing 30% glycerol (Sigma-Aldrich, St.…”
Section: Escherichia Coli Isolate Sourcementioning
confidence: 99%
“…The first study was initiated by The South African Department of Agriculture and Water Research Commission to help characterize the bacterial quality of South African irrigation water (Aijuka et al, 2015). A high prevalence of faecal indicators within milk sold by unregulated retailers alarmed the South African Dairy Development Agency which subsequently initiated the second study to characterize its microbiological quality (Ntuli et al, 2017(Ntuli et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Ntuli, Njage, and Buys () reported that the prevalence of E. coli O157:H7 in bulk milk samples was in the range of 2%, varied from 13% in Australian, 0.02–2.4% in U.S. and 0.7% in Greek. Zhang et al () investigated 183 chicken samples in 4 provinces (14 cities) of South China by plate count method, and the prevalence of E. coli O157:H7 was 3.28%.…”
Section: Resultsmentioning
confidence: 99%
“…Another is that VT2-producing E. coli has many serotypes and all are regarded as pathogens, although O157 predominates. The primers designed according to VT2 gene can detect any bacteria carrying VT2 gene(Hara-Kudo et al, 2007) Ntuli, Njage, and Buys (2016). reported that the prevalence of E. coli O157:H7 in bulk milk samples was in the range of 2%, varied from 13% in Australian, 0.02-2.4% in U.S. and 0.7% in Greek Zhang et al (2015).…”
mentioning
confidence: 99%